Delusional belief flexibility and informal caregiving relationships in psychosis: a potential cognitive route for the protective effect of social support. (December 2014) - Jolley, S.; Ferner, H.; Bebbington, P.; Garety, P.; Dunn, G.; Freeman, D.; Fowler, D.; Kuipers, E.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. For people with psychosis, contact with informal caregivers is an important source of social support, associated with recovery, and with better outcomes following individual cognitive therapy (CBTp). In this study, we tested whether increased flexibility in delusional thinking, an established predictor of positive outcome following CBTp, was a possible mechanism underlying this effect. Methods. 219 participants with delusions (mean age 38 years; 71% male; 75% White) were grouped according to the presence of a caregiver (37% with a caregiver) and caregiver level of expressed emotion (High/Low EE, 64% Low). Delusional belief flexibility was compared between groups, controlling for interpersonal functioning, severity of psychotic symptoms, and other hypothesised outcome predictors. Results. Participants with caregivers were nearly three times more likely than those without to show flexibility (OR = 2.7, 95% CI 1.5 to 5.0, p = 0.001), and five times more likely if the caregiving relationship was Low EE (OR = 5.0, 95% CI 2.0–13.0, p = 0.001). ORs remained consistent irrespective of controlling for interpersonal functioning and other predictors of outcome. Conclusions. This is the first evidence that having supportive caregiving relationships is associated with a specific cognitive attribute in people with psychosis, suggesting a potential cognitive mechanism by which outcomes following CBTp, and perhaps more generally, are improved by social support.